Age-related decrease in motor contribution to multisensory reaction times in primary school children - Alhamdan, Areej A.; Murphy, Melanie J.; Crewther, Sheila G. (Frontiers in Human Neuroscience, 2022)
Traditional measurement of multisensory facilitation in tasks such as speeded motor reaction tasks (MRT) consistently show age-related improvement during early childhood. However, the extent to which motor function increase with age and hence contributes to multisensory motor reaction times in young children has seldom been examined. Thus, we aimed to investigate the contribution of motor development to measures of multisensory (auditory, visual and audiovisual) and visuomotor processing tasks in three young school age groups of children (n = 69) aged (5-6, n = 21; 7-8, n = 25.; 9 -10 n = 18 years). We also aimed to determine whether age-related sensory threshold times for purely visual inspection time (IT) tasks improved significantly with age. Bayesian results showed decisive evidence for age-group differences in multisensory MRT and visuo-motor processing tasks, though the evidence showed that threshold time for visual identification IT performance was only slower in the youngest age group children (5-6) compared to older groups. Bayesian correlations between performance on the multisensory MRT and visuo-motor processing tasks indicated moderate to decisive evidence in favour of the alternative hypothesis (BF10= 4.71 to 91.346), though not with the threshold IT (BF10 <1.35). This suggests that visual sensory system development in children older than 6 years makes a less significant contribution to the measure of multisensory facilitation, compared to motor development. In addition to this main finding, multisensory facilitation of MRT within race-model predictions was only found in the oldest group of children (9-10), supporting previous suggestions that multisensory integration is likely to continue into late childhood/ early adolescence at least.